Variation in gut microbial communities of Chilo suppressalis in the typical bivoltine areas of northern China. (21st April 2022) - Zhang, Jingtong; Chen, Chen; Zhu, Kexin; Ma, Haotian; Fu, Zhanyu; Tan, Hao; Wang, Xingya
Abstract: The gut microbiota play an important role in digestion, development, nutritional metabolism and detoxification in insects. The rice stem borer, Chilo suppressalis, is one of the most destructive rice pests and has caused serious economic losses to major rice‐producing areas of China. However, little is known about how its gut microbiota has adapted to different geographical environments. We investigated the gut microbiota of C .  suppressalis populations collected from five sites in the typical areas of northern China using 16S rDNA gene sequencing on an Illumina MiSeq platform. In total, 453, 853, 707 reads and 1650 operational taxonomic units (OTUs) in 25 gut samples of C .  suppressalis were obtained. We identified 697 bacterial genera from 30 phyla, and Proteobacteria and Firmicutes were the most dominant phyla. Gut bacterial richness and alpha‐diversity metrics revealed no significant differences among these populations. We detected the highest bacterial diversity in Beizhen, western Liaoning Province. Principal coordinates analysis (PCoA) and clustering analysis (UPGMA) showed no distinct gut microbial community structure of C .  suppressalis in these regions. Linear discriminant analysis (LDA) effect size (LEfSe) indicated that the bacterial species exhibited significant differences among the middle, northern and western regions. Finally, PICRUSt analysis demonstrated that microbial functions closely associated with the gut microbiome mainly included membrane transport, amino acid metabolism and carbohydrate metabolism. Accordingly, our study provided important insights into the investigation of insect‐bacteria symbioses and evaluated gut microorganisms as biocontrol agents for this pest and other agricultural lepidopterans.